2020
DOI: 10.1177/0886260520967128
|View full text |Cite
|
Sign up to set email alerts
|

Me and Others Around: The Roles of Personal and Social Norms in Chinese Adolescent Bystanders’ Responses Toward Cyberbullying

Abstract: Researchers have expanded the aggressor-victim dyad by showing that bystanders play pivotal roles in the process of cyberbullying. Bystanders’ responses entail moral engagement and are guided by personal and social norms. Most research on normative influences on bystanders’ responses to cyberbullying has focused on personal or social norms but has ignored how they jointly affect bystanders’ responses. Inspiring by the modified Theory of Planned Behavior, a cross-sectional study of Chinese high-school students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
2
7
0
Order By: Relevance
“…These results are consistent with those obtained in previous studies between the justification of violence belief and bystanders’ behavior (Machackova & Pfetsch, 2016; Walters & Espelage, 2021). Additionally, cyberbully reinforcers and assistants had the highest scores in CB perpetration, indicating that those who support the aggressors are also the ones who attack on other occasions (Dang & Liu, 2020; Van Cleemput et al, 2014). Also, outsiders scored higher than victim defenders both in justification of violence and CB perpetration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results are consistent with those obtained in previous studies between the justification of violence belief and bystanders’ behavior (Machackova & Pfetsch, 2016; Walters & Espelage, 2021). Additionally, cyberbully reinforcers and assistants had the highest scores in CB perpetration, indicating that those who support the aggressors are also the ones who attack on other occasions (Dang & Liu, 2020; Van Cleemput et al, 2014). Also, outsiders scored higher than victim defenders both in justification of violence and CB perpetration.…”
Section: Discussionmentioning
confidence: 99%
“…Limited research on the relationship between cyberbystanders' reactions and their CB perpetration offers interesting findings. Generally, being a cyberbully has proven to be an important predictor of reinforcing the aggressor when witnessing CB (Barlińska et al, 2013(Barlińska et al, , 2015Dang & Liu, 2020;Van Cleemput et al, 2014). For example, in a cross-sectional study with 333 Chinese adolescents, CB perpetration was related to intentions to reinforce the bully (Dang & Liu, 2020).…”
Section: Cyberbullying and Justification Of Violencementioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, this is the first study that focuses on this variable with this operationalization in cyberbullying contexts. There has been little research regarding this issue in cyberbullying contexts ( Palladino et al., 2017 ) and recent literature has revealed that pro-cyberbullying personal and social norms could negatively influence bystanders’ intentions to help victims ( Dang and Liu, 2022 ). In fact, bystanders’ personal and social norms could interact to predict behavioral intentions to reinforce bullying behavior.…”
Section: How Bystander’ Normative Beliefs Of Perceived Severity Of Cy...mentioning
confidence: 99%